Defences for defamation: its strengths and weaknesses / Fatimah Zahrah Ramli …[et al.] - Ramli, Fatimah Zahrah; Rosalan, Nurliyana; Abd. Hadi, Rozanna; Mohamed Rahim, Siti Baqiuratul Zahraa' (2006)
The tort of defamation is principally designed to protect interest in reputation from untrue statements. There are a number of important and extremely complex defences to defamation, and the complexity reflects the difficulty in satisfying the desire to balance the need for freedom of speech against the need to protect the reputation of the individual. The defences that are discussed in this research are the unintentional defamation, justification, fair comment and privilege. These defences will be considered in detail and careful note should be made in particular circumstances in which each may apply. A defence is said to be effective if the defendant can put a bar against any legal proceedings in defamation instituted by the plaintiff. Meanwhile, a defence is said to be ineffective if the plaintiff can successfully claim for remedies from the defendant. Hence, in corresponding with the objective of this research, these defences will be examined as to their strengths and weaknesses. This is to find out whether these defences are effective or not either in theory or in practice.